2012
DOI: 10.1186/1746-160x-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Condylar volume and condylar area in class I, class II and class III young adult subjects

Abstract: AimAim of this study was to compare the volume and the shape of mandibular condyles in a Caucasian young adult population, with different skeletal pattern.Material and methods200 Caucasian patients (15–30 years old, 95 male and 105 females) were classified in three groups on the base of ANB angle: skeletal class I (65 patients), skeletal class II (70 patients) and skeletal class III (65 patients). Left and right TMJs of each subject were evaluated independently with CBCT (Iluma). TMJ evaluation included: condy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 18 publications
(16 reference statements)
10
79
5
3
Order By: Relevance
“…In some research it has been demonstrated that no important differences are observed in soft tissue when facial class II and class III are compared. In this study we observed some differences in the lower lip position related to the retraced position of the mandible ; furthermore, it has been confirmed that mandible condyle morphology in TMJ (temporo mandibular joint) shows differences when comparing subjects with facial class II or facial class III (Muñoz et al, 2014a(Muñoz et al, , 2014b; this can justify differences in TMJ response after skeletal surgery by physiopathology of the TMJ (Saccucci et al, 2012).…”
Section: Introductionmentioning
confidence: 61%
“…In some research it has been demonstrated that no important differences are observed in soft tissue when facial class II and class III are compared. In this study we observed some differences in the lower lip position related to the retraced position of the mandible ; furthermore, it has been confirmed that mandible condyle morphology in TMJ (temporo mandibular joint) shows differences when comparing subjects with facial class II or facial class III (Muñoz et al, 2014a(Muñoz et al, , 2014b; this can justify differences in TMJ response after skeletal surgery by physiopathology of the TMJ (Saccucci et al, 2012).…”
Section: Introductionmentioning
confidence: 61%
“…De hecho, otro estudio de Saccucci et al (2012b) determino que el tamaño y volumen condilar son significativamente diferentes en sujetos clase I, clase II y clase III lo cual puede generar la discusión sobre el papel que cumple el cóndilo en la consecutiva deformidad facial; así, el cóndilo seria capaz de generar o potenciar cierto tipo de deformidades, mientras que por otra parte, las condiciones funcionales podrían acentuar también patologías condilares como en situaciones donde la reducción de la carga oclusal permite la disminución del volumen óseo condilar en ambos sexos y la disminución de la maduración de condrocitos exclusivamente en mujeres (Chen et al 2011). Esta información redunda en una relación de causa y efecto que podría ser bidireccional en la relación de la deformidad facial y el cóndilo mandibular.…”
Section: Discussionunclassified
“…Condylar dimensions and position in the fossa are more frequently affected in older compared to younger patients. 5 Consequently, the sample was selected according to this criterion, in order to evaluate patients without condylar alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Initial sample estimate was 58 CBCTs (power 80%, α of 0.05, sample size ratio of 1.70). Finally, a total of 124 CBCTs from 18-30 yearold patients were selected, 5 and classified into two groups (n=62) for Class II and Class III skeletal patterns. CBCTs from patients with bilateral molar occlusal contacts were included in the study.…”
Section: Methodsmentioning
confidence: 99%